Review: Study the Role of China Acupuncture and "GI" Acupuncture as an Alternative and Complementary Therapy in the Treatment - Risna Agustina; Andreanus A. Soemardji; Felesia Fanty; Lia Amalia (Journal of Tropical Pharmacy and Chemistry, 2019)
This article discusses the scientific literature review on Chinese acupuncture and "GI" acupuncture as an attempt therapy many cases, besides that specifically studied the effectiveness of traditional acupuncture china to stress with "GI" acupuncture. Chinese acupuncture is an acupuncture method that was developed in China since ± 2000 years ago, while "GI" acupuncture is a method of acupuncture that was developed at the Institute Technology Bandung by acupuncturists Gunawan Ismail (Alm) is slightly different from the traditional Chinese acupuncture, where acupuncture "GI "based on a 7 acupuncture points on the body for ase points determined based of Java massage. Each method studied acupuncture and its role as a therapeutic efforts on a variety of cases, and the results of the study showed some success in handling cases of diseases such as fibromyalgia, stroke and stress. The role of acupuncture GI who want to see here is give the same effectiveness with traditional acupuncture originated from China or even better.